2014
DOI: 10.1007/s00248-014-0441-2
|View full text |Cite|
|
Sign up to set email alerts
|

Linking Host Prokaryotic Physiology to Viral Lifestyle Dynamics in a Temperate Freshwater Lake (Lake Pavin, France)

Abstract: In aquatic ecosystems, fluctuations in environmental conditions and prokaryotic host physiological states can strongly affect the dynamics of viral life strategies. The influence of prokaryote physiology and environmental factors on viral replication cycles (lytic and lysogeny) was investigated from April to September 2011 at three different strata (epi, meta, and hypolimnion) in the mixolimnion of deep volcanic temperate freshwater Lake Pavin (France). Overall, the euphotic region (epi and metalimnion) was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Although mitomycin C dosage may be tailored in single-strain systems, when dosing mixed communities an unknown proportion of organisms or lineages may be underdosed, overdosed or correctly dosed at any given dose 11 . Although it is unclear what any FCIC value really means, the observed variability in FCIC may be indicative of the taxonomic or physiological state of organisms in a given sample 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Although mitomycin C dosage may be tailored in single-strain systems, when dosing mixed communities an unknown proportion of organisms or lineages may be underdosed, overdosed or correctly dosed at any given dose 11 . Although it is unclear what any FCIC value really means, the observed variability in FCIC may be indicative of the taxonomic or physiological state of organisms in a given sample 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption of DOM and nutrients to BC particles may also create microniches that could serve as hot spots for microbial activity (though our data were not collected on a scale to reveal such activity). Ultimately, by impacting the physiological state of bacteria and their overall community metabolism, the bacterial utilization of black carbon becomes a potential factor influencing viral life strategies in aquatic systems (Maurice et al, 2013;Palesse et al, 2014). Previous reports have suggested that virally mediated bacterial mortality decreases with an increase in BC concentration (Mari et al, 2014;Malits et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that proviruses are common within prokaryotic communities with some results suggesting that 60% of bacteria harbour at least one prophage (Casjens, 2003;Edwards & Rohwer, 2005) and others reporting that the frequency of lysogeny in marine bacteria is 40% (Jiang & Paul, 1994Paul, 2008), between 0.1 and 16% in temperate lakes and between 0 and 73% in Antarctic lakes (Sime-Ngando & Colombet, 2009). Recent studies suggest that lysogeny may represent a transitional state or stress response to abiotic changes experienced by hosts (Palesse et al, 2014). However, explanations of results on lysogeny remain ambiguous (Weinbauer, 2004).…”
Section: (1) Factors Enhancing Vprmentioning
confidence: 97%